Study on effect of high temperature stress in wheat genotypes using SDS protein profile - Satbhai, Ravindra (Journal of Cereal Research, 2016)
This study was carried out in order to investigate the effects of heat stress on SDS-Protein profile in wheat (Triticum aestivum L.). Ten wheat genotypes differing in thermotolerance were first grown in natural day light condition for 10 days and then seedlings were shifted to BOD at a temperature 25Â± 1â°C for 24 h, and subsequently gradually exposed to 300C for 1h, 350C for 1h, 400C for 2h and at 460C for 3h. Genetic variability assayed by cell viability test revealed that wheat genotypes NIAW-34 and AKAW-4627 lowest TTC reduction and higher cell viability were considered as thermotolerant genotypes. The study revealed that SDS-PAGE protein profile exhibited new set of proteins when exposed to sub lethal to lethal heat stress (400C for 2h to 460C for 3h). Small molecular weight proteins appeared with different intensity during temperature induction treatments. Protein with 60 kDa size and 14 kDa size areÂ observed constantly in all thermotolerant wheat cultivars during high temperature stress. Proteins with 7 and 11.2 kDa size are also observed at 460C for 3h heat stress in thermotolerant NIAW-34 and AKAW-4627 and in thermo-susceptible wheat NIAW-917. It is also observed that normal wheat seedlings when shifted to temperature above five or more optimum growth temperature (250C) synthesis of most normal proteins was repressed and translation of new protein was induced.